Identifikasi kandungan fucoidan yang diekstrak dari Sargassum sp. yang diambil dari Pantai Pantai Sundak, Gunung Kidul - Muahiddah, Nuri; Rahmadani, Thoy Batun Citra (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2024)
This study aims to identify the fucoidan content extracted from Sargassum sp. collected from Sundak Beach, Gunung Kidul. Fucoidan is a sulfated polysaccharide compound with various biological activities, including anticoagulant, antitumor, and anti-inflammatory activities. Sargassum sp. was chosen as the source of fucoidan due to its abundance in coastal waters and its pharmacological potential. The extraction method was carried out using a hot water extraction technique with acid treatment, followed by a purification process using dialysis. The extracted fucoidan content was then analyzed using spectrophotometry and Thin Layer Chromatography (TLC) to determine its concentration and purity. Fourier Transform Infrared (FTIR) spectroscopy was used to identify the functional groups of the compound. The results showed that fucoidan was successfully extracted from Sargassum sp. with a significant yield. The main component of the extracted fucoidan from Sargassum sp. in this study was fucose, as indicated by the TLC results. The Rf value of the fucoidan hydrolysate from Sargassum sp. and the standard fucoidan, which was 0.51, matched that of fucose, indicating that both samples contained fucose. This study concludes that Sargassum sp. from Sundak Beach, Gunung Kidul, is a potential source for high-quality fucoidan production.